Opportunities and Threats of the MOOC Movement for Higher Education: The European Perspective - Schuwer, Robert; Gil-Jaurena, Inés; Aydin, Cengiz Hakan; Costello, Eamon; Dalsgaard, Christian; Brown, Mark; Jansen, Darco; Teixeira, Antonio (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The Massive Open Online Course (MOOC) movement is the latest ‘big thing’ in Open and Distance Learning (ODL) which threatens to transform Higher Education. Both opportunities and threats are extensively discussed in literature, comprising issues on opening up education for the whole world, pedagogy and online versus campus education. Most of the literature focus on the origin of the MOOC movement in the US. The specific context of Europe with on the one hand autonomous countries and educational systems and on the other hand cross-border cooperation and regulations through the European Union differs from the US context. This specific context can influence the way in which the MOOC movement affect education in Europe, both reusing MOOCs from other continents (US) as publishing MOOCs, on a European platform or outside of Europe. In the context of the EU funded HOME project, a research was conducted to identify opportunities and threats of the MOOC movement on the European institutions of higher education. Three sources of data were gathered and analysed. Opportunities and threats were categorized in two levels. The macro level comprises issues related to the higher education system, European context, historical period and institutional level. The micro level covers aspects related to faculty, professors and courses, thus to the operational level. The main opportunities mentioned were the ECTS system as being a sound base for formal recognition of accomplishments in MOOCs, the tendency to cooperate between institutions, stimulated by EU funded programs and the many innovative pedagogical models used in MOOCs published in Europe. The main threats mentioned were a lacking implementation of the ECTS system, hindering bridging non/formal and formal education and too much regulation, hindering experimenting and innovation.